Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/jcm12031155
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis on the 2D:4D Digit Ratio and Its Relationship with Social Responsiveness in Adults with Prader–Willi Syndrome

Abstract: Prader–Willi syndrome (PWS) is a genetic disorder produced by a lack of expression of paternally derived genes in the 15q11–13 region. Research has generally focused on its genetic and behavioral expression, but only a few studies have examined epigenetic influences. Prenatal testosterone or the maternal testosterone-to-estradiol ratio (MaTtEr) has been suggested to play an important role in the development of the ‘social brain’ during pregnancy. Some studies propose the 2D:4D digit ratio of the hand as an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Another limitation of our study pertains to individuals with disabilities. Previous studies have shown that certain pathologies and disabilities can interfere with the 2D:4D ratio (Gámez et al, 2023), as well as psychiatric disorders (Fusar-Poli et al, 2021;Nieuwoudt et al, 2021;Paipa et al, 2018), and other medical conditions (Arazi et al, 2023). Additionally, our study only included male participants, and therefore, it remains unclear how these findings would generalize to female participants.…”
Section: Discussionmentioning
confidence: 94%
“…Another limitation of our study pertains to individuals with disabilities. Previous studies have shown that certain pathologies and disabilities can interfere with the 2D:4D ratio (Gámez et al, 2023), as well as psychiatric disorders (Fusar-Poli et al, 2021;Nieuwoudt et al, 2021;Paipa et al, 2018), and other medical conditions (Arazi et al, 2023). Additionally, our study only included male participants, and therefore, it remains unclear how these findings would generalize to female participants.…”
Section: Discussionmentioning
confidence: 94%